Human Dentinal Tubules alterations after desensitizing Dentifrices use: An ex vivo study - Rafael Lima Pedro; Luise Gomes da Motta; Marcelo de Castro Costa (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
Objective: Evaluated the effects of desensitizing dentifrices on dentinal tubule occlusion in human teeth thought qualitative and quantitative analysis. Methods: Eighty dentin block were divided in eight groups, two controls (positive and negative) and six using desenstitizing dentifrices (Colgate Pro-alívio®, Colgate Tripla Ação®, Colgate Sensitivity®, Sensodyne Repair & Protect®, Sensodyne dentes sensíveis® and Cariax®) The specimens were storaged in natural saliva. A simulated toothbrushing machine were used corresponding 21 brushings weekly and used six cicles. For qualitative analysis Scanning Eletronic Microscopy (SEM) and Energy-Dispersive X-ray Epectroscopy (EDS) were used. Percentage of occluded tubules was obtained for quantitative analisys. The data were statistically analyzed by ANOVA and Tukey tests (p < 0.05). Results: Colgate Pro-alívio®, Colgate Sensitivity®, Sensodyne Repair & Protect® and Sensodyne dentes sensíveis® showed better effect in occluded dentinal tubules (p<0.05), the slurry on dental surface were differents depending of active principle of samples and EDS showed presence of calcium and phosphorus in all groups. Conclusion: All dentifrices were able to occluded dentinal tubules and Calcium and phosphorus were a regular found, however Cariax® andColgate Tripla Ação® had the worst results in quantitative analyses.